ETHNOBOTANICAL AND BIOLOGICAL ACTIVITIES OF Leptadenia pyrotechnica (Forssk.) Decne.: A REVIEW - Idrees, Saiba; Qureshi, Rahmatullah; Bibi, Yameen; Ishfaq, Aqsa; Khalid, Nadia; Iftikhar, Anam; Shabir, Anam; Riaz, Iqra; Saboon, Nil; Ahmad, Nabeela (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Leptadenia pyrotechnica is traditionally used for treating various diseases. This species holds variety of bioactive constituents that trigger healing properties. The present review was aimed to analyze nutritional, phytochemical and pharmacological activities of L. pyrotechnica. Materials and Methods: The present review regarding Leptadenia pyrotechnica (Forssk.) Decne. Is the compilation of data from the previous research works conducted by various scientists across the world. Various published papers, medicinal plant databases,etc were utilized to compile the information. Results: L. pyrotechnica is a wonderful desert plant belongs to the family Asclepiadaceae This plant possesses antifungal, antibacterial, anticancer, antioxidant, wound healing, anthelmintic, antiatheroscloretic, hypolipidemic, antdiabetic and hepatoprotective activities coupled with other multifarious uses. Almost all plant parts are used in the traditional medicinal system to treat various disorders. Conclusion: This review includes the substance of different ethnobotanical uses, phytochemistry and exclusive capability of this plant in the field of anti-microbial and human disease activities.